SISTEM ROUTING PROSES DELIVERY MENGGUNAKAN SIMULATED ANNEALING (Studi Kasus: PT. X) - Budi Nur Siswanto; Afferdhy Ariffien; Ilham Jayakusuma (JURNAL TEKNOLOGIA, 2019)
The development of e-commerce and intelligent transportation systems makes logistics activities an important and ever increasing part of people's lives. The speed of freight transportation makes logistics companies more competitive and the costs incurred for distribution are issues of concern. Couriers in a delivery company are one of the main operational strengths, so the determination of the route must be well defined. This study discusses the creation of routing system and proposed business processes for the delivery company (PT. X) by applying the Asymmetric Capacitated Vehicle Routing Problem (ACVRP) using Simulated Annealing metaheuristic algorithm with a trade-off between the total distance and the maximum distance of one route 0.1; 0.5; and 0.9. The routing system optimization is adjusted to the needs of the decision maker to focus its route determination, whether it is focused on the total distance or the maximum distance of one route. The proposed business process can saves as much as 2 hours.